Potentialities of the ultrasonography by detection of the acromion types as external cause of impingment syndrome - A. Yu. Kinzersky; I. N. Turdakina (Бюллетень сибирской медицины, 2011)
It is on record that the curved and hooked acromion types result in the lesion in the rotator cuff tendons. Research aim: to increase the informational content of ultrasound investigation of a glenohumeral joint using ultrasonic analysis of acromial morphology. To research is based on the comparison of radiographic findings of the acromion with the length of coraco-acromial ligament. Altogether 112 patients aged from 21 to 80 which complained the shoulder pain were examined. Among them there were 76 (67,9%) women and 36 (32,1%) men.The length of the coracoacromial ligament was defined for each type of acromion process.Conclusion: we found ultrasound equivalent (the length of coracoacromial ligament) for each type of acromion, which allows to reduce radiation exposure of the patients while their examination.